VARIABLE-RATE STEGANOGRAPHY USING RGB STEGO-IMAGES - Abdalla, Ayman M. (European Scientific Journal, ESJ, 2013)
A new algorithm is presented for hiding information in the least significant bits of color images. The number of bits used for hiding changes according to pixel neighborhood information where less resemblance between a pixel and its neighbors leads to using more bits for hiding. Experimental results are presented to show that the algorithm generally hides information with a good capacity while avoiding detection.